Prevalence of Left ventricular diastolic dysfunction in newly diagnosed and never treated essential hypertension in tertiary care Hospital of Nepal - Gajurel, RM; Sayami, A (Journal of Institute of Medicine Nepal, 2015)
Introduction: Hypertension is a global public health problem with one fourth adults worldwide estimated to have high blood pressure (BP).1 The incidence of hypertension continues to increase in all developed and developing societies as the population grows older and more obese.2 The Framingham Study and other epidemiological surveys have clearly defined HTN as an important cause of morbidity and mortality. 2-3 the aim of this study was to determine the prevalence of Left ventricular diastolic dysfunction in newly diagnosed and never treated essential hypertension.Methods: A cross sectional study was used for those patients who were attended outpatient clinic of Man Mohan centre with diagnosis of newly diagnosed and never treated hypertension over a period of October 2011 to November 2012.Results: A total of 130 essential hypertensive patients underwent trans-thoracic echocardiography for evaluation of left ventricular diastolic function. Among 130 consecutive cases 56(43.1%) had normal Left ventricular diastolic function in echocardiography, 22(16.9%) patients had grade I LVDD, 50(38.5%) had grade II LVDD and 2 (1.5%) patients had grade IIIa LV diastolic dysfunction.Conclusion: LV diastolic dysfunction was found to have very common preclinical myocardial dysfunction even in new and never treated essential hypertension.